Abyssal deposit feeders are secondary consumers of detritus and rely on nutrition derived from microbial communities in their guts - Sonia Romero-Romero; Lee C. Miller; Jesse A. Black; Brian N. Popp; Jeffrey C. Drazen (Scientific Reports)
Abstract Trophic ecology of detrital-based food webs is still poorly understood. Abyssal plains depend entirely on detritus and are among the most understudied ecosystems, with deposit feeders dominating megafaunal communities. We used compound-specific stable isotope ratios of amino acids (CSIA-AA) to estimate the trophic position of three abundant species of deposit feeders collected from the abyssal plain of the Northeast Pacific (Station M; ~ 4000 m depth), and compared it to the trophic position of their gut contents and the surrounding sediments. Our results suggest that detritus forms the base of the food web and gut contents of deposit feeders have a trophic position consistent with primary consumers and are largely composed of a living biomass of heterotrophic prokaryotes. Subsequently, deposit feeders are a trophic level above their gut contents making them secondary consumers of detritus on the abyssal plain. Based on δ13C values of essential amino acids, we found that gut contents of deposit feeders are distinct from the surrounding surface detritus and form a unique food source, which was assimilated by the deposit feeders primarily in periods of low food supply. Overall, our results show that the guts of deposit feeders constitute hotspots of organic matter on the abyssal plain that occupy one trophic level above detritus, increasing the food-chain length in this detritus-based ecosystem.